(untitled) (Journal of Engineering, 2011)
The piled raft is a geotechnical composite construction consisting of three elements: piles, raft and soil. In the design of piled rafts, the load shared between the piles and the raft, and the piles are used up to a load level that can be of the same order of magnitude as the bearing capacity of a comparable single pile or even greater. Therefore, the piled raft foundation allows reduction of settlements in a very economic way as compared to traditional foundation concepts. This paper presents experimental study to investigate the behavior of piled raft system in sandy soil. A small scale “prototype” model was tested in a sand box with load applied to the system through a compression machine. The settlement was measured at the center of the raft, strain gages were used to measure the strains and calculate the total load carried by piles. Four configurations of piles (2x1, 3x1, 2x2 and 3x2) were tested in the laboratory, in addition to rafts with different sizes. The effects of pile length, pile diameter, and raft thickness on the load carrying capacity of the piled raft system are included in the load-settlement presentation. It was found that the percentage of the load carried by piles to the total applied load of the groups (2x1, 3x1, 2x2, 3x2) with raft thickness of 5 mm, pile diameter of 9 mm, and pile length of 200 mm was 28% , 38% , 56% , 79% , respectively. The percent of the load carried by piles increases with the increase of number of piles.